Dynamics, control, and flying qualities of V/STOL aircraft - Franklin, James A. (American Institute of Aeronautics and Astronautics, 2002)
Annotation This text presents the principles of dynamics and control for vertical, short take-off landing (V/STOL) aircraft. It is the first book of its kind. It is intended for graduate students and professionals in aeronautics who have knowledge of linear systems analysis, aircraft static, dynamic stability, and control. The text begins with a discussion of V/STOL aircraft operations. Control strategies, equations of motion, longitudinal and lateral-directional flying qualities in both hover and forward flight, wind and turbulence responses, and control augmentation and cockpit displays are covered. Specific examples of the YAV-8B Harrier and XV-15 Tilt Rotor aircraft are used to illustrate actual V/STOL dynamic and control characteristics
Keywords: Vertically rising aircraft.; Short take-off and landing aircraft.; Short take-off and landing aircraft -- Handling characteristics.; Airplanes -- Control systems.; elektronické knihy; electronic books